10.1002/9781118797914 (CrossRef Listing of Deleted DOIs, 2000)
INTRODUCTION: Sustaining interventions implemented as part of pragmatic clinical trials requires proactive planning, but how to approach this process remains understudied. The Non-pharmacological Options in Hospital-based and Rehabilitation pain Management stepped-wedge cluster-randomized pragmatic trial tested an electronic health record-based educational bundle (known as the Healing After Surgery [HAS] initiative) that encouraged the incorporation of non-pharmacological pain care in perioperative pain management. The HAS initiative was implemented in multiple surgical practices and hospital sites. One year prior to trial completion, a sustainment committee was established to support the transition of intervention components to clinical ownership and to support posttrial sustainment of the HAS initiative. METHODS: We reviewed meeting minutes from biweekly sustainment committee meetings and conducted debriefing sessions with committee members (informed by the Clinical Sustainability Assessment Tool) to identify sustainment strategies and challenges, which were then organized into meaningful themes. RESULTS: The following six themes emerged from meeting minutes and debriefings: (1) automation of low-touch components, (2) reliance on internal champions, (3) intentional handoff communication, (4) institutional attention, (5) relaxed fidelity, and (6) continuous evaluation. Together, they highlight the importance of early, structured planning and adaptable implementation strategies. CONCLUSIONS: Sustainment of the HAS initiative required extensive communication, adaptation, and stakeholder engagement across diverse institutional contexts. Proactive sustainment planning during trial design may help ensure interventions are successfully integrated into routine clinical practice posttrial.